2006
DOI: 10.1097/01.ta.0000198469.95292.ec
|View full text |Cite
|
Sign up to set email alerts
|

Does the Rate of Rewarming from Profound Hypothermic Arrest Influence the Outcome in a Swine Model of Lethal Hemorrhage?

Abstract: Rapid induction of hypothermic arrest maintains viability of brain during repair of lethal vascular injuries. Long-term survival is influenced by the rate of reversal of hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 49 publications
1
55
1
3
Order By: Relevance
“…A hypothermic cardiac arrest offers the possibility of survival because of the effects of rapid cooling. Hypothermia causes a decrease in cellular oxygen demand, which is advantageous during periods of ischemia [15]. Cardiac surgeons take advantage of controlled hypothermia to perform surgery under circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothermic cardiac arrest offers the possibility of survival because of the effects of rapid cooling. Hypothermia causes a decrease in cellular oxygen demand, which is advantageous during periods of ischemia [15]. Cardiac surgeons take advantage of controlled hypothermia to perform surgery under circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothermic cardiac arrest offers the possibility of survival because of the effects of rapid cooling. Hypothermia causes a decrease in cellular oxygen demand, which is advantageous during periods of ischemia [9]. Cardiac surgeons take advantage of controlled hypothermia to perform surgery under circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, they showed that profound hypothermia could be used successfully, even after 60 min of normothermic shock, and that the surviving animals were not only neurologically intact but also had normal cognitive functions. Subsequent studies showed that the best outcomes were achieved using rapid induction of hypothermia (2 °C/min) and a slower rate of reversal (0.5 °C/min warming) [70,86]. Moreover, these studies using Unisol solutions for implementing HBS demonstrated the preservation of various cell types in the central nervous system, in addition to providing some immunological advantages [87,88].…”
Section: Recent Advances Using a Pre-clinical Porcine Hemorrhagic Shomentioning
confidence: 99%